## Solving the Equation (x-6)(x-6) = 0

This equation represents a simple quadratic equation in factored form. To solve for the value of *x*, we can utilize the following steps:

### Understanding the Equation

The equation (x-6)(x-6) = 0 represents the product of two identical factors, (x-6) and (x-6), equaling zero.

### The Zero Product Property

The **Zero Product Property** states that if the product of two or more factors is zero, then at least one of the factors must be zero.

### Solving for x

Applying the Zero Product Property to our equation, we have:

**(x-6) = 0**

Solving for *x* in this equation:

- x = 6

Since both factors are identical, the solution *x = 6* is a **double root** for the equation.

### Conclusion

The equation (x-6)(x-6) = 0 has one solution, *x = 6*, which is a double root. This means the solution *x = 6* satisfies the equation twice.